Answers

2014-10-04T21:56:55+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the second stone overtakes the first stone t seconds after the first stone is dropped.

height covered by first stone = 0.5gt²
height covered by second stone = v(t-n)+0.5g(t-n)²
Both heights are equal. Thus
0.5gt² = v(t-n)+0.5g(t-n)²
⇒0.5gt² = vt - vn + 0.5g(t²-2tn+n²)
⇒0.5gt² = vt - vn + 0.5gt² - gtn + 0.5gn²
⇒vt - vn - gtn + 0.5gn² = 0
⇒t(v-gn) - vn + 0.5gn² = 0
⇒t(v-gn) = vn - 0.5gn²

⇒ t =  \frac{vn-0.5gn^{2} }{v-gn}

Distance travelled = 0.5gt² = 0.5g [\frac{vn-0.5gn^{2} }{v-gn}  ]^{2}
0